Translating clinical trial outcomes measures : an overview - Tyupa, Sergiy; Wild, Diane (SEEd Medical Publishers, 2016)
The purpose of this book is to provide a general overview of the translation and cultural adaptation process of clinical research survey instruments with a focus on the linguistic aspects of the process. This book is made up of two parts. The first part offers a brief introduction to selected linguistic aspects of translation. The second part describes the main steps used in the translation process.